Law and the "Sharing Economy" Regulating Online Market Platforms - McKee, Derek; Makela, Finn; Scassa, Teresa (Law, Technology and Media, 2018)
The rapid expansion of sharing economy platforms such as Airbnb and Uber has generated enormous controversy. This book brings legal and interdisciplinary perspectives to the labour, market and technology and other regulatory challenges that arise from this phenomenon that has taken the world by storm.